Effect of Low Dose Aspirin in Low Risk Pregnant Ladies with Abnormal Uterine Artery Doppler Results, and the Evaluation of Maternal and Fetal outcomes: A Randomized Clinical Trial - Parzhin Jalal Ali; Chro Najmaddin Fattah (Kurdistan Journal of Applied Research)
This study aimed to identify the effect of low dose aspirin administration in low risk pregnant ladies who have abnormal uterine artery Doppler results. Patients and Methods: A randomized clinical trial was performed on 50 pregnant ladies (?16 weeks of gestation) in Sulaymaniyah Maternity Teaching Hospital during January 2017 to January 2018. The participants were randomly enrolled into two groups; the participants in the first group were given 100 mg of aspirin tablet each but the other group was given nothing. Results: Preeclampsia was significantly (P-value of <0.001) less in the aspirin group as compared to the other group (16% and 40% respectively). The pulsatility index (PI) was not significantly different in both the groups (P-value = 0.69), but resistance index (RI) was significantly lower in the aspirin group (P-value of <0.001). Conclusion: Doppler study of the uterine artery at 16 weeks or higher in low risk pregnant women appears to be useful as a screening test and low dose of aspirin therapy at early stage of pregnancy will decrease the incidence of preeclampsia.